Secreted Toxins From Staphylococcus aureus Strains Isolated From Keratinocyte Skin Cancers Mediate Pro-tumorigenic Inflammatory Responses in the Skin - Krueger, Annika; Zaugg, Julian; Chisholm, Sarah; Linedale, Richard; Lachner, Nancy; Teoh, Siok Min; Tuong, Zewen K.; Lukowski, Samuel W.; Morrison, Mark; Soyer, H. Peter; Hugenholtz, Philip; Hill, Michelle M.; et al. (Frontiers in Microbiology, 2022)
Squamous cell carcinoma (SCC) is a common type of skin cancer that typically arises from premalignant precursor lesions named actinic keratoses (AK). Chronic inflammation is a well-known promoter of skin cancer progression. AK and SCC have been associated with an overabundance of the bacterium Staphylococcus aureus (S. aureus). Certain secreted products from S. aureus are known to promote cutaneous pro-inflammatory responses, however, not all S. aureus strains produce these. As inflammation plays a key role in SCC development, we investigated the pro-inflammatory potential and toxin secretion profiles of skin-cancer associated S. aureus. Sterile culture supernatants (‘secretomes’) of S. aureus clinical strains isolated from AK and SCC were applied to human keratinocytes in vitro. Some S. aureus secretomes induced keratinocytes to overexpress inflammatory mediators that have been linked to skin carcinogenesis, including IL-6, IL-8, and TNFα. A large phenotypic variation between the tested clinical strains was observed. Strains that are highly pro-inflammatory in vitro also caused more pronounced skin inflammation in mice. Proteomic characterization of S. aureus secretomes using mass spectrometry established that specific S. aureus toxins and enzymes, including haemolysins and serine proteases, as well as currently uncharacterized proteins, correlate with the pro-inflammatory S. aureus phenotype. This study is the first to describe the toxin secretion profiles of AK and SCC-associated S. aureus, and their potential to induce a pro-inflammatory environment in the skin. Further studies are needed to establish whether these S. aureus products promote SCC development by mediating chronic inflammation.